Automatic Adjustment of the Inspiratory Trigger and Cycling-Off Criteria Improved Patient-Ventilator Asynchrony During Pressure Support Ventilation - Liu, Ling; Yu, Yue; Xu, Xiaoting; Sun, Qin; Qiu, Haibo; Chiumello, Davide; Yang, Yi (Frontiers in Medicine, 2021)
BACKGROUND: Patient-ventilator asynchrony is common during pressure support ventilation (PSV) because of the constant cycling-off criteria and variation of respiratory system mechanical properties in individual patients. Automatic adjustment of inspiratory triggers and cycling-off criteria based on waveforms might be a useful tool to improve patient-ventilator asynchrony during PSV. METHOD: Twenty-four patients with were enrolled and were ventilated using PSV with different cycling-off criteria of 10% (PS10), 30% (PS30), 50% (PS50), and automatic adjustment PSV (PSAUTO). Patient-ventilator interactions were measured. RESULTS: The total asynchrony index and NeuroSync index were consistently lower in PSAUTO when compared with PS10, PS30, and PS50, (P < 0.05). The benefit of PSAUTO in reducing the total asynchrony index was mainly because of the reduction of the micro asynchrony index but not the macro asynchrony index. PSAuto significantly improved the relative cycling-off error when compared with prefixed controlled PSV (P < 0.05). PSAuto significantly reduced the trigger error and inspiratory effort for trigger when compared with a prefixed trigger. However, total inspiratory effort, breathing patterns, and respiratory drive were not different among modes. CONCLUSIONS: When compared with fixed cycling-off criteria, an automatic adjustment system improved patient-ventilator asynchrony without changes in breathing patterns during PSV. The automatic adjustment system could be a useful tool to titrate more personalized mechanical ventilation.